Special Education in Perspective: Implications for Articulated Teaching in High School and Technological - Costas, Fabiane Adela Tonetto; Honnef, Claucia (Education Policy Analysis Archives, 2015)
Articulated teaching is proposed as an adaptation to collaborative teaching and aims the joint work between the regular class teacher and the special education teacher in planning, developing and evaluating a class. The aim of this study was to analyze how high school teachers and technology education teachers of a Federal Education Institute in Rio Grande do Sul, Brazil, realize articulated teaching, what their limitations and possibilities are before the inclusion of students with disabilities and/or special educational needs, intensified after the National Policy of Special Education (2008). The research was qualitative, using a field diary and a questionnaire answered by seven professors from a student with intellectual disabilities included in the medium and technology education. To interpret the data we used in Content Analysis. The results showed that articulated teaching is important, however, few teachers have cited difficulties in performing it, for example, the low number of special education teachers and regular class teachers, and little time to this work. We conclude that the articulated teaching has obstacles to overcome, but we believe in its potential to mobilize learning, particularly for pupils with special educational needs, through special education in the perspective of inclusive education, which in the current educational context massified the idea of inclusive school education, with no sufficient investment to ensure conditions for it to be extended to all subjects.